PATIENTS’ LIFE QUALITY DYNAMICS UPON OPTIMIZING THE IMPLANT PROSTHODONTICS AND THEIR ATTITUDE TO THE RESULTS OF DENTAL ORTHOPAEDIC TREATMENT (SOCIOLOGIC ANALYSIS) - V. N. Trezubov; O. A. Volkovoy; E. A. Bulycheva; A. V. Konchakovskiy; Ju. V. Alpatyeva (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2017)
The life quality estimation of dental patients, especially with total adentia, before and after implant treatment is highly topical. A direct or immediate implant prosthodontics contributes to prompt restoration of impaired aesthetic and functional standards while urgently converting patients from a disability level to a high life quality category. However, mistakes and complications occurring in this treatment stage often result in patients’ discomfort and worsen their physical and psycho-emotional state. All these are not conductive to securely provided favourable results of dental implant prosthetics, and thus require further improvement of the clinical and conceptual approaches aimed at further optimization of the above specialized medical care. The authors succeeded in improving efficacy of immediate implant prosthodontics with extended orthopaedic constructions by means of optimizing the diagnostic and therapeutic resources, as well as the hygiene protocol.